2021
DOI: 10.1111/jre.12869
|View full text |Cite
|
Sign up to set email alerts
|

A new mixed model of periodontitis‐induced preeclampsia: A pilot study

Abstract: Objectives/Background: Recent studies have shown that periodontal disease is strongly related to gestational complications such as preeclampsia (PE). PE is responsible for 42% of maternal deaths worldwide and kills approximately 76 000 women a year. In addition, children born under PE conditions are at increased risk of hospitalization due to metabolic disorders, epilepsy, and other complications. Numerous reviews and clinical studies on PE have been published, but the mechanisms underlying the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…SH9H-2020-A358-1) and conformed to the ARRIVE (Animal Research: Reporting of In Vivo Experiments) guidelines. A sample of 8 animals per group was used (Mata et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…SH9H-2020-A358-1) and conformed to the ARRIVE (Animal Research: Reporting of In Vivo Experiments) guidelines. A sample of 8 animals per group was used (Mata et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…During the second trimester, pregnant women are at higher risk of hypertension, clinically evident in 8% of pregnant patients ( Barr et al, 2022 ), characterized by poorer oral health and a higher incidence of complications with local anesthesia ( Mata et al, 2021 ). During dental treatment, fear and pain are the most common causes of high blood pressure.…”
Section: Survey Methodologymentioning
confidence: 99%
“…A cross-sectional study recording clinical periodontal parameters and assessing serum C-reactive protein levels confirmed that poor maternal periodontal status, increased oral inflammatory burden and increased systemic inflammation had an adverse effect on infant birth weight ( 18 ). In addition, it was suggested that periodontal infection could exacerbate the progression of pre-eclampsia, and periodontal disease was considered to be one of the risk factors for pre-eclampsia ( 19 , 20 ).…”
Section: The Association Between Periodontal Disease and Adverse Preg...mentioning
confidence: 99%